Interelasi Akal dan Wahyu: Analisis Pemikiran Ulama Mutakallimin dalam Pembentukan Hukum Islam: Interelasi Akal dan Wahyu: Analisis Pemikiran Ulama Mutakallimin dalam Pembentukan Hukum Islam - Kawakib, Kawakib; Syuhud, Hafidz (Institut Agama Islam Negeri (IAIN) Pontianak, 2021)
This paper aims to reveal and analyze the thoughts of Mutakallimin scholars on the interpretation of reason and revelation in the formation of Islamic law, which has been a debate. The debate was caused by several factors, including the understanding of the Quran and Sunnah texts, dwellings, social, and culture. In this article, the author finds that Mutakallimin scholars agree that the answer to Islamic law problems cannot be separated from the first source, namely the Quran and the Sunnah. If the Alquran and Sunnah are not found, then Mutakalimin scholars agree to use ijtihad and qiyas. Ijtihad and qiyas are the results of the mujtahid’s reasoning towards Allah SWT's revelations, whose meaning is still unclear, global, and general to reveal the purpose and purpose Allah's revelation regarding the problems of everyday human life. Thus, the Mutakalimin scholars position human reason in the formation of Islamic law as a mediation of the argument of ‘aqliyah to answer everyday human problems in worship, zakat, muamalah, economics, and politics. Besides, Mutakallimin scholars have different Islamic legal, methodological concepts, but the primary sources in forming mutually agreed upon Islamic law are the Alquran, Sunnah, ijma’, and qiyas. Ijma’ and qiyas here have an essential role in the mind's intellect towards revelation so that they can become a bridge in the formation of laws to answer human problems along with the place and era.